2017
DOI: 10.1186/s40634-017-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine reduces the inhibition of proteoglycan metabolism caused by local anaesthetic solution in human articular cartilage: an in vitro study

Abstract: BackgroundWe assessed whether local anaesthetics caused inhibition of proteoglycan metabolism in human articular cartilage and whether the addition of Glucosamine sulphate could prevent or allow recovery from this adverse effect on articular cartilage metabolism.MethodsCartilage explants obtained from 13 femoral heads from fracture neck of femur patients (average age 80 years, 10 female) were exposed to either 1% Lidocaine, 2% Lidocaine, 0.25% Bupivacaine, 0.5% Bupivacaine, 0.5% Levo-bupivacaine or a control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Gulihar and Shaunak [12] showed that all local anesthetics tested inhibited proteoglycan metabolism in articular cartilage and that glucosamine was able to reduce the inhibition. Glucosamine produces GAG, which is able to protect the articular cartilage [12]. These findings suggest that chondrocytes remain functional because GAG can protect chondrocyte function after exposure to local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gulihar and Shaunak [12] showed that all local anesthetics tested inhibited proteoglycan metabolism in articular cartilage and that glucosamine was able to reduce the inhibition. Glucosamine produces GAG, which is able to protect the articular cartilage [12]. These findings suggest that chondrocytes remain functional because GAG can protect chondrocyte function after exposure to local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Bupivacaine acts directly on the extracellular matrix, resulting in dermatan sulfate production [11]. Gulihar and Shaunak [12] showed that all local anesthetics tested inhibited proteoglycan metabolism in articular cartilage and that glucosamine was able to reduce the inhibition. Glucosamine produces GAG, which is able to protect the articular cartilage [12].…”
Section: Discussionmentioning
confidence: 99%